Development of Professional Ethics Training Program for Educators to Improve the Quality of Education - Nurumairah; Tumini; Abdul Rahman Marjuki; Syafaatul Habib; Khrisfision (Penerbit Hellow Pustaka, 2025)
To improve the standard of education, this Journal discusses the creation of a professional ethics training program for teachers. Teachers must have a strong understanding of professional ethics to provide a supportive and professional learning environment in this increasingly complex era of education. This study involved educators from various levels of education and used a qualitative approach using a case study method. According to the study's findings, professional ethics training helped teachers become more connected to their students while increasing their knowledge of their professional responsibilities. The curriculum consisted of a number of interactive courses that addressed the professional, social, and moral elements of teaching. The evaluation revealed that participants' attitudes and actions changed significantly, which improved the quality of teaching. The results of the study confirm the value of professional ethics education as a tactic to improve the standard of education in Indonesia. It is hoped that the findings of this study will serve as a guide for creating similar initiatives in other academic settings.